2019
DOI: 10.12998/wjcc.v7.i22.3728
|View full text |Cite
|
Sign up to set email alerts
|

Super-selective arterial embolization in the control of acute lower gastrointestinal hemorrhage

Abstract: BACKGROUNDAcute gastrointestinal bleeding is an emergency condition that can lead to significant morbidity and mortality. Embolization is considered the preferred therapy in the treatment of lower gastrointestinal bleeding when it is unrealistic to perform the surgery or vasopressin infusion in this population. Treatment of acute lower gastrointestinal (GI) bleeding (any site below the ligament of Treitz) using this technique has not reached a consensus, because of the belief that the risk of intestinal infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Recently, TAE has been proven effective for the treatment of acute gastrointestinal bleeding, with high technical success and acceptable clinical success rates. Published studies have reported varying technical success rates ranging from 97 to 100% [ 4 8 , 14 17 ]. The major advantage of TAE is its ability to control severe bleeding without bowel preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, TAE has been proven effective for the treatment of acute gastrointestinal bleeding, with high technical success and acceptable clinical success rates. Published studies have reported varying technical success rates ranging from 97 to 100% [ 4 8 , 14 17 ]. The major advantage of TAE is its ability to control severe bleeding without bowel preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al showed that among 175 patients with lower gastrointestinal bleeding who achieved technical success, 86.1% and 6.1% achieved clinical success and developed major complications, respectively [ 15 ]. Bowel ischemia or infarction has been the most severe complication of TAE, although their published incidence rates have remained quite low [ 4 8 , 14 17 ]. One study showed that cases developing bowel infarction exhibit a 90% increase in their mortality rate during hospital stay [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arterial embolization (AE) is an angiographic technique aimed to reduce the vascular supply of a bone lesion by selectively occluding its feeding arteries [ 17 , 18 , 19 ]. The injection of embolizing material is performed in order to only occlude the feeding vessels of the lesion, avoiding damage to the adjacent structures [ 20 , 21 , 22 ]. As mentioned above, skeletal-related events in patients with bone metastases can affect the quality of life.…”
Section: Embolizationmentioning
confidence: 99%
“…The rate at which angiography detects an active bleeding site has been shown to depend on the bleeding rate, with the required bleeding rate of minimum 0.5 mL/min (Strate, 2005;Yoon et al, 2006). With technological improvements in super selective embolization of distal artery branches in interventional angiography, it has become an effective method for controlling upper GI bleeding quickly and safely (Hreinsson et al, 2016;Lv and Gu, 2019). However, significant complications may be seen in 3% of cases.…”
Section: Angiographymentioning
confidence: 99%